Realkalization of corroded rebar in mortar with monoethanolamine as a corrosion inhibitor: influence of total charge and applied electric field on repair effectiveness - Yunyun Tong; Ziwei Li; Mengya Li; Jinjian Ye; Jiong Wang; Jianqiao Chen; Wei Mao; Wei Zeng (Journal of Asian Architecture and Building Engineering)
The realkalization process is an electrochemical technique to restore and enhance the pH level in carbonated concrete. This study investigated the effectiveness of realkalization using an alkaline solution (K2CO3) with monoethanolamine (MEA) as a corrosion inhibitor. Reinforced mortar specimens were subjected to accelerated carbonation, followed by accelerated corrosion of the embedded steel rebars. During the repair process, MEA was used to increase the polarization resistance of the rebar and provided surface protection. The effectiveness was evaluated by monitoring the corrosion potential and corrosion current density at various total electric charges. Comparative experiments without the electric field were also conducted. After repair, the pH values, potassium ions (K+) concentrations, and MEA contents of the mortar cover were measured. The results showed that the corrosion potential shifted positively, while the corrosion current density decreased, indicating a reduction in corrosion activity. Electrochemical and analytic results exhibited that a total charge of at least 150 A·h/m2 was required for effective repair. However, the long-time effectiveness was limited, as the steel rebars remained in a moderate corrosion state.